The diet of feral goats (Capra hircus L.) in the Rimu-Rata-Kamahi Forest of Mount Egmont [microform] : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology at Massey University - Mitchell, Russell John (Massey University, 1985)
The diet of the feral goat (Capra hircus) in rimu-rata-kamahi forest on Mount Egmont was examined by sorting monthly rumen samples for one year. Seasonal changes in diet, relative plant palatabilities, differential fragmentation and digestion rates of plant species, nitrogen and mineral levels in principal foods, and several aspects of population biology were measured. Results show that individual goats contain at least 19 plant species on average and some more than 30. Presumably, they eat about this number daily. However, just two species (Asplenium bulbiferum and Ripogonum scandens) make up 44.8% of the total amount eaten over the year. There are significant seasonal changes in the amounts eaten for Coprosma grandifolius, Coprosma tenuifolia, Griselinia littoralis, Melicytus ramiflorus, Ripogonum scandens (fruit and vine) and Weinmannia racemosa. Goats clearly select or reject different plant species. Thus use of species is largely independent of availability. The most preferred foods are probably Schefflera digitata and Ripogonum scandens fruit and vine. In contrast the very abundant Microlaena spp., Uncinia spp., moss, Alsophila smithii and especially Blechnum fluviatile are among the most unpalatable. The low and probably variable availability of many species within the study area obscures their seasonal trends and palatability ratings. Asplenium bulbiferum, and probably Melicytus ramiflorus, are underestimated in the diet, whereas Ripogonum scandens vine may be overestimated. However, the magnitude of error is not sufficient to be a problem in this study. There is no obvious correlation between diet selection and the levels in plants of N, K, Ca, Mg, P, s, Cu, Zn, Fe and Mn. Only Na is deficient enough to possibly be selected for and highest levels occur in the very palatable Schefflera digitata. Age structure, body condition and reproductive data suggest a predominantly young, healthy population that is reproducing rapidly.
Keywords: New Zealand Goats; Feeding and feeds